Analysis Of The Influence Of Company Size, Good Corporate Governance And Profitability On The Value Of Idx-30 Companies Listed On The Indonesian Stock Exchange - Uli Wildan Nuryanto; Lailatun Nafisa; Ahmad Junaidi; Mustangin; Suyadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to determine whether a company's size, profitability, and level of corporate governance affect its overall value. The method that the researchers in this study have selected is called purposeful sampling. The IDX-30 enterprises that are listed on the Indonesia Stock Exchange comprise the population of this study. The data used in this study are secondary. Two methods are available to researchers for gathering the data for analysis: documentation and a review of existing literature. This study's analytical approach makes use of quantitative analysis methods that are handled by SPSS. This study employed traditional assumption test analysis, model testing, and hypothesis testing. The following conclusion can be drawn from the presented research results: The value of the corporation is unaffected by good corporate governance as demonstrated by independent commissioners. There is no correlation between management ownership and good corporate governance and the value of the company. There is no correlation between institutional ownership and good corporate governance and a company's worth. The ROA's projection of profitability affects the company's worth. The ROE's projection of profitability raises the value of the enterprise. The worth of a corporation is independent of its size.